2020
DOI: 10.3892/mmr.2020.11383
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of Scavenger receptor class B type�I: A�protective molecule and a facilitator of atherosclerosis (Review)

Abstract: The scavenger receptor class B type i (Sr-Bi) is a multi-ligand membrane protein receptor that binds to high-density lipoprotein (Hdl) under physiological conditions, promoting the selective uptake of cholesterol esters from Hdl into cells. Sr-Bi also promotes the reverse transport of excess cholesterol from peripheral tissues to the liver, contributing to the synthesis of bile acids for excretion and the removal of excess cholesterol from the body, thereby lowering the cholesterol load and exerting anti-ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…SR-BI binds to HDL and promotes the reverse transport of excess cholesterol from peripheral tissues to the liver ( Ma et al, 2020 ). In this study, simvastatin and CM1 administration had no effect on the protein expression of SR-BI ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SR-BI binds to HDL and promotes the reverse transport of excess cholesterol from peripheral tissues to the liver ( Ma et al, 2020 ). In this study, simvastatin and CM1 administration had no effect on the protein expression of SR-BI ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…The elevated levels of apoAI and HDL-C may enhance the cholesterol accepting capacity of the plasma. Although CM1 had no effect on SR-BI, which is a key receptor for liver uptake of HDL particles ( Ma et al, 2020 ), this molecule may increase SR-BI-mediated cholesterol clearance due to the increased apoAI and HDL-C levels in CM1 treatment group. Furthermore, CM1 administration significantly reduced the mRNA, but not protein, level of SREBP-2, which modulates cholesterol synthesis ( Moslehi and Hamidi-Zad, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, CM1 may reduce plasma TC by enhancing reverse cholesterol transport. SR-BI and LDLR mediate cholesterol transport from lipoproteins to the liver, contributing to a reduction of plasma TC [ 16 , 27 , 36 ]. A recent study suggested that CM1 can enhance the expression of SR-B1 protein in apoE (−/−) mice [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol regulation of SR-B1 has also been demonstrated through SREBP and LXR functions implicating that multiple signaling pathways participate in SR-B1 expression [ 182 ]. Its allelic variants are linked to an increased risk of atherosclerosis [ 193 ], infertility [ 194 ], and/or an impaired innate immune response [ 195 , 196 , 197 ].…”
Section: Sr-b1mentioning
confidence: 99%